Allelopathic potential of Myrtle, Myrtus communis L. Upon some crops (Baghdad Science Journal, 2012)
Many experiments were achieved to determine the allelopathic potential of the plant Myrtle parts in which it may affects other plants, like: volatile substances which released from the Myrtle leaves , and its effect examined on the germination (GE) and growth (GR) of the selected crops ; Chickpea ( C ) , Wheat(W) , and Lentil (L)., the aqueous extract of the leaf and the root of the plant examined to test its effect on the (GE) and (GR) of the selected crops ; (C) , (W) , and (L)., also plant residue of (M) and its effect tested on the (GE) and (GR) of the selected crops ; ( C ) , (W) , and (L) . Experiments proceeded on Spring 2007 in the greenhouse conditions , and main results which found were that; the effect of the volatile substances released from the Myrtle plant was so great and reached significant levels in all cases and with all tested crops .Whereas, the effect of the other pathways were only in an obvious states and only in the following cases reached a significant levels which were; - the case of the effect of the plant residue on the(GR) of root , shoot , and seedlings of the selected crops ; ( C ),(W) ,and ( L) .-the case of the effect of the plant residue on the (GR) of (W) seeds. The case of the effect of the aqueous extract of the root of the Myrtle plant on the (GE) of the (C ) seeds ?- And finally, the case of the effect of the aqueous extract of the root on the (GR) of the root, shoot, and the seedlings of (L).